Catalytic Polymer Multilayer Shell Motors for Separation of Organics. Issue 5 (22nd December 2015) - Lin, Zhihua; Wu, Zhiguang; Lin, Xiankun; He, Qiang
Abstract: A catalytic polymer multilayer shell motor has been developed, which effects fast motion‐based separation of charged organics in water. The shell motors are fabricated by sputtering platinum onto the exposed surface of silica templates embedded in Parafilm, followed by layer‐by‐layer assembly of polyelectrolyte multilayers to the templates. The catalytic shell motors display high bubble propulsion with speeds of up to 260 μm s −1 (13 body lengths per second). Moreover, the polyelectrolyte multilayers assembled at high pH (pH>9.0) adsorb approximately 89 % of dye molecules from water, owing to the electrostatic interaction between the positively charged polymers and the anionic dye molecules, and subsequently release them at neutral pH in a microfluidic device. The efficient propulsion coupled with the effective adsorption behavior of the catalytic shell motors in a microfluidic device results in accelerated separation of organics in water and thus holds considerable promise for water analysis. Abstract : Wee shells will be moved : A catalytic polymer multilayer shell motor has been developed, which displays high bubble propulsion with speeds of up to 260 μm s −1 . Moreover, the polyelectrolyte multilayers adsorb anionic dye molecules from water. The efficient propulsion coupled with the effective adsorption behavior of the catalytic shell motors in a microfluidic device results in accelerated separation of organics in water (see figure).